Strategi Pemberdayaan Masyarakat di Masa Pandemi melalui Program Peduli Dampak Corona (APDC) di LAZ Dompet Dhuafa Cabang Malang - Muhamad Faiz Abudalisa; M. Hafiar Baidlowi (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2021)
This study intends to provide a formulation of community empowerment strategies during the pandemic which is carried out by the Malang branch of the Dompet Dhu'afa zakat institution. So far, every zakat institution has focused programs on the community (not only mustahik), but the program is only sudden and not programmed. However, the community empowerment strategy carried out by Dompet Dhu'afa was very effective because it was followed by an accurate management pattern, proportional-based programs and economic development. This is important to research, considering that a community empowerment strategy has not been formulated which has become a national pilot in the midst of a weakening world economy. This research is a descriptive qualitative study with a phenomenological approach to social institutions. All data are primary and extracted based on interview and documentation guidelines, in the final stage it is presented after going through the triangulation process. From the results of this study, several important things were found, namely the implementation of the Aksi peduli Dampak Corona program (APDC) during the Covid-19 pandemic, namely: 1) fish farming in artificial ponds, a freshwater fish cultivation program managed directly by the surrounding community. using artificial pond media, 2) Empowered Farmers are farming activities in the form of local vegetables and fruits which are commodities in the Malang region. Which in turn is managed directly by the surrounding community and directly supervised by experts from planting, maintenance, harvesting, to marketing, 3) Animal husbandry is one of the Corona Impact Care Action movements, here Dompet Dhuafa East Java presents approximately 30 sheep to be managed by surrounding communities affected by this pandemic as well as the stock for distributing the Sacrificial Animal Spread program next year.